Influence of Teacher Support and Personal Relevance on Academic Self-Efficacy and Enjoyment of Mathematics Lessons: A Structural Equation Modeling Approach - Aldridge, Jill M.; Afari, Ernest; Fraser, Barry J. (Alberta Journal of Educational Research, 2013)
The purpose of our study was to examine the effects of two psychosocial features of the classroom environment (teacher support and personal relevance) on college students’ academic self-efficacy and enjoyment of mathematics lessons. Data collected from 352 mathematics students attending three higher education institutions in the United Arab Emirates were used to validate the questionnaires and to investigate the hypothesized relationships. Structural equation modeling analysis suggests that teacher support and personal relevance are influential predictors of enjoyment of mathematics lessons and academic self-efficacy. L’objectif de cette étude est d’examiner les effets de deux facteurs psychosociaux de la salle de classe (soutien des enseignants et pertinence personnelle) sur l’auto-efficacité académique des étudiants universitaires et du plaisir qu’ils retirent des cours de mathématiques. On a puisé dans des données recueillies chez 352 étudiants en mathématiques de trois institutions d’études supérieures aux Émirats arabes unis pour valider les questionnaires et vérifier les relations postulées. Une analyse de la modélisation par équation structurelle laisse supposer que le soutien des enseignants et la pertinence personnelle ont constitué des facteurs de prévision influents quant au plaisir que retirent les étudiants des cours de mathématiques et à leur auto-efficacité académique. <input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function')jsCall();elsesetTimeout('jsCall()',500);" type="hidden" /><input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function')jsCall();elsesetTimeout('jsCall()',500);" type="hidden" /><input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function')jsCall();elsesetTimeout('jsCall()',500);" type="hidden" /><input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function')jsCall();elsesetTimeout('jsCall()',500);" type="hidden" /><input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function')jsCall();elsesetTimeout('jsCall()',500);" type="hidden" /><input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function')jsCall();elsesetTimeout('jsCall()',500);" type="hidden" /><input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function')jsCall();elsesetTimeout('jsCall()',500);" type="hidden" /><input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function')jsCall();elsesetTimeout('jsCall()',500);" type="hidden" /><input id="gwProxy" type="hidden" /><input id="jsProxy" onclick="if(typeof(jsCall)=='function')jsCall();elsesetTimeout('jsCall()',500);" type="hidden" />